An examination of the psychometric properties of the chinese coach-athlete relationship questionnaire (CART-Q) - Xin Yang, S.; Jowett, S. (International Journal of Coaching Science, 2010)
The present study aimed to explore the psychometric properties of the Coach-Athlete Relationship Questionnaire (CART-Q) in the Chinese language. Based on the 3+1Cs of the coach-athlete relationship conceptual model (Jowett, 2007a), the CART-Q aims to measure three interpersonal psychological constructs, namely: closeness, commitment, and complementarity from a direct perspective and a meta-perspective (see Jowett, 2009). This study examined the factorial validity of both direct and meta-perspective versions of the translated CART-Q in the Chinese language with a sample of 246 elite Chinese athletes by using confirmatory factor analysis. Its concurrent validity was also examined via a three-step mediation analysis using structural equation modelling. Overall, findings provided tenable support for the validity and reliability of the two CART-Q versions within the Chinese coach-athlete relationship context. The possibility of subtle cultural variations in the multidimensional conception of coach-athlete relationships are discussed alongside implications for theory, research, and practice.